Group composition of diesel fuel as a factor of different susceptibility of low-temperature additives; Химия и химическая технология в XXI веке - Bogdanov I. A. Ilya Aleksandrovich (Химия и химическая технология на иностранном языке, 2019)
Заглавие с экрана